Relationship between moral identity and parenting styles on prosocial behavior among youth in Selangor, Malaysia - Hasbullah, Najah; Ma’rof, Aini Azeqa; Dahamat Azam, Mohamad Naqiuddin (Human Resources Management Academic Research Society (HRMARS), 2024)
This study investigates the influence of parenting styles, namely authoritarian, authoritative, and permissive, as well as moral identity, on the growth of altruism in young individuals. Gathering data from a broad sample of volunteers, a quantitative technique was used to analyse the influence of several factors on altruistic behaviours. The study utilised regression analysis to examine the predictive efficacy of each parenting style and moral identity on altruism, offering a nuanced comprehension of the interplay between these factors within a socio-cultural framework. The results indicate that both authoritarian and permissive parenting styles have a significant correlation with the cultivation of altruistic behaviour in young individuals. Contrary to expectations based on Western research, this study found no significant relationship between the authoritative parenting style and altruistic behaviours. Similarly, this study did not find a significant relationship between moral identity and altruism, indicating that the influence of personal moral standards may be intricate and influenced by unaccounted factors. The findings highlight the importance of cultural context in influencing the efficacy of different parenting approaches. According to this study, both authoritarian and permissive parenting styles can promote altruistic behaviour. However, the specific ways in which these styles influence prosocial behaviour may vary depending on cultural norms and particular family dynamics. These findings question the idea that authoritarian parenting is universally the most successful style and emphasise the importance of considering cultural factors when studying the development of compassion. This study adds to the wider discussion on moral development and parenting, urging for additional research on the interplay between specific elements of parenting and individual moral identity in shaping prosocial behaviours such as altruism. These insights are essential for creating customised educational and parental practices that effectively encourage altruistic behaviours in various cultural contexts.